Describing Consumerâ€™s Desire to Share Positive Information (Positive WOM) Based on the experience Stayed at Hotel Sahid Montana Dua - Nazir, Mehran Aniq (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aimed to describe consumers' desire for information delivery is positive (positive WOM) based on the experience of staying at Hotel Sahid Montana Dua. This study uses quantitative methods with descriptive type of research that explains consumers' desire for positive WOM delivery based on the experience stayed with three votes ratings.Methods of data collection using questionnaires and interviews, and internet browsing. Samples obtained were 30 respondents who represent the Hotel Sahid Montana Dua Malang who have stayed for one night at minimal. This study uses the NPS (Net Promoter Score) as a data analysis tool.Based on the results of data processing using NPS, consumers will make a positive WOM will experience earned during a stay at Hotel Sahid Montana Dua Malang.Â Keywords: service, customer, customer experience, positive WOM, Hotel Sahid Montana Dua